工業地域河口に生息しているカキ(Crassostrea gigas)のトリクロロ酢酸による汚染 - 後藤 政幸; ゴトウ マサユキ; Masayuki GOTOH (和洋女子大学家政学部健康栄養学科, 2007)
Biomonitoring using oysters was done to assess environmental pollution due to trichloroacetic acid (TCA). The data in 2001, in oysters from the Koe River and the Ariho River at the industrial sea areas, TCA was detected at 97 and 40 ng/g in the average, but trichloroethanol (TCE) was not detected. TCA concentrations in 2004 were at 175 and 59 ng/g, respectively. And, TCE was not detected. This data shows a TCA concentration increase of about 48-80% over a three year period. This result may be caused by the bioconcentration and/or biometabolism in oysters. If the bioconcentration has increased, the environmental biomonitoring of TCA using oysters should be one means to facilitate obtaining data on water pollution due to TCA.